A Key Ingredient in Deforestation Slowdowns? A Strong Brazilian Economy - Richards, Peter (Frontiers in Forests and Global Change, 2021)
For much of the past two decades, the scientific and policy community has sought to reduce forest loss through well-targeted public policy and enforcement measures and private sector engagement. Unfortunately, recent increases in forest loss in the Amazon have raised new concerns over the drivers of deforestation in the region, and the durability of the policies designed to mitigate it. Here we argue that recent deforestation trends are a partial reflection of Brazil’s economic trajectories. More specifically, in this short article we show that, all else being equal, economic stagnation in Brazil, via its influence on the value of the Brazilian currency, the real, positively influences local prices for export products and increases farm level incentives for land clearing. Conversely, economic growth, nationally, suppresses prices and land clearing incentives. Ultimately, we argue that, at the national-scale, economic growth may be closely aligned with, and possibly a precondition to, the attainment of international or national-level environmental goals.